Surgical Management of Optic Disc Pit Maculopathy - Akhwand Abdul Najeed Jawad, Harron Tayyab, Tehmina Jahangir (Pakistan Journal of Ophthalmology, 2016)
Purpose: To evaluate the structural and functional outcome of pars plana vitrectomy combined with ILM peel, endo-photocoagulation and gas tamponade for optic disc pit associated maculopathy. Study Design: Prospective interventional case series Place and Duration of Study: Jinnah Hospital Lahore and Al-Ehsan Eye Hospital Lahore Material and Methods: Seven consecutive patients with unilateral maculopathy associated with optic disc pit underwent pars plana vitrectomy combined with ILM peel, endo- photocoagulation and gas tamponade. Patients were followed up for 6 months after treatment. Main outcomes were determined by optical coherence tomography (OCT) and best – corrected visual acuity (BCVA). Results: Treatment with C3F8 tamponade followed by laser photocoagulation in ODP maculopathy patients resulted in resolution of sub-retinal and/or intra-retinal fluid in six out of seven patients at the end of six month follow up. The remaining one patient had significant reduction in retinoschisis, as determined by OCT, and fundoscopy, as well as an improvement in anatomical architecture. There was statistically significant improvement in visual acuity in four eyes, remained stable in two eyes and deteriorated in one eye in which we were not able to achieve complete macular reattachment at the end of six months. Central visual field loss after photocoagulation was not clinically appreciable. No post- operative complications of maculopathy occurred during the follow-up period. Conclusion: Given the myriad underlying pathology of sub retinal and intra retinal fluid secondary to optic disc pit associated maculopathy, a complete procedure of pars plana vitrectomy combined with ILM peel, endo-photocoagulation and gas tamponade proved to be an efficient procedure to achieve satisfactory structural and functional out come. Key words: Optic disc pit maculopathy, retinoschisis, photocoagulation, pars plana vitrectomy, internal limiting membrane.